Triglycerides to apolipoprotein A1 ratio: an effective insulin resistance-associated index in identifying metabolic dysfunction-associated fatty liver disease in type 2 diabetes mellitus - Wang, Wei; Chen, Yang; Tu, Mei; Chen, Hang Ju (Frontiers in Endocrinology, 2024)
BackgroundThe triglycerides to Apolipoprotein A1 ratio (TG/APOA1) holds promise to be a more valuable index of insulin resistance for the diagnosis of metabolic dysfunction-associated fatty liver disease (MAFLD) in type 2 diabetes mellitus (T2DM). This study aims to evaluate the correlation between TG/APOA1 and MAFLD, as well as compare the efficacy of TG/APOA1 with triglycerides to high-density lipoprotein cholesterol ratio (TG/HDL-c) and triglyceride-glucose (TyG) index in identifying MAFLD among individuals with T2DM.MethodThis study consecutively recruited 779 individuals with T2DM for the investigation. The unenhanced abdominal CT scans were conducted to measure CT liver-spleen attenuation measurement (CTL-S). The CTL-S less than 1.0 and without other liver comorbidities were considered to be MAFLD. The binomial logistic regression analysis and restricted cubic spines (RCS) were employed to evaluate the association between TG/APOA1 and MAFLD. The receiver operating characteristic (ROC) curve analysis was performed to compare the efficacy of TG/APOA1 with TG/HDL-c and TyG index identifying MAFLD.ResultsThe TG/APOA1 exhibited a substantial increase in the MAFLD group (P<0.05). Even after adjustments for potential confounding factors, TG/APOA1 exhibited significant associations with nonalcoholic fatty liver disease fibrosis score (β=0.266, P<0.001), fibrosis-4 index (β=0.123, P=0.029), aspartate aminotransferase-to-platelet ratio index (β=0.113, P=0.037), and CTL-S (β=-0.225, P<0.001). Meanwhile, TG/APOA1 contributed to an independent variable for MAFLD, the odds ratio with a 95% CI was 2.092 (1.840-2.380) in the total population, 2.123 (1.810-2.511) in men, and 2.162 (1.824-2.587) in women. Additionally, the results also revealed a nonlinear association between elevated TG/APOA1 and higher MAFLD risk according to the RCS analysis whether in the total population, men, or women (P for nonlinearity and overall <0.001). Furthermore, TG/APOA1 had higher AUC level compared to TG/HDL-c and TyG index in the total population (0.769 vs 0.742, P=0.025; 0.769 vs 0.694, P < 0.001), men (0.776 vs 0.744, P=0.044; 0.776 vs 0.709, P < 0.001), and women (0.762 vs 0.728, P=0.041; 0.762 vs 0.674, P < 0.001).ConclusionTG/APOA1 serves as an effective index of insulin resistance in identifying MAFLD, offering advantages in the screening of MAFLD in T2DM.